Significant Calcification of an Entire Aortic Tree with Renal Artery Subocclusion: Acute Kidney Injury, Ischemic Kidney Disease, and the Tissue Viability Question—A Case Report - Marko Baralić; Selena Gajić; Aleksandra Kezić; Ana Bontić; Jelena Pavlović; Voin Brković; Vidna Karadžić Ristanović; Danka Bjelić; Maja Životić; Sanja Radojević-Škodrić; Želimir Antonić; Nenad Ilijevski; et al. (Life)
Background: Undiagnosed and untreated atherosclerotic renal artery stenosis (ARAS) can result in end-stage kidney disease (ESKD). To obtain an accurate diagnosis, it is crucial to recognize the symptoms and signs suggesting renal artery stenosis (RAS) and perform appropriate diagnostic and treatment procedures afterward. Case Presentation: We present a case of a 60-year-old female patient with hypertensive crisis, acute heart failure (HF), and pulmonary edema as the initial signs of acute kidney injury (AKI) caused by right RAS and left renal artery occlusion in the presence of severe aortic atherosclerosis revealed on computed tomography angiography (CTA) of the abdomen. The patient’s renal function recovered completely following percutaneous transluminal angioplasty (PTA) with stent implantation in the right renal artery at the site of subocclusion. Conclusions: Even in patients with concomitant disorders like type-2 diabetes mellitus (T2DM), hypertension (HTN), or HF, the dilatation of significantly narrowed renal arteries due to severe calcifications can result in complete renal function recovery.